(untitled) (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
This article aimed to verify the validity of the Kuznets hypothesis for Brazilian cities in 1991, 2000 and 2010. Kuznets (1955) suggests that economic development in its early stages is accompanied with the increase in income inequality, up to a maximum point, and then decreases as the economy develops a curve in a graphic pattern of inverted "U" shape. The study investigates this hypothesis by applying panel data, using information from the Atlas of Brazil Human Development (PNDU, 2013), using the Gini coefficient and Theil L as measures of inequality and per capita income as a measure of growth. The results indicate that the Kuznets hypothesis is accepted under some particularizations, but is rejected in a more general model.